A Study on Vegetable Market atVizhulupuram District with special reference to Tamilnadu - THAGAPILLAI, L.; ARAVAZHI, Dr. D. (IJRDO - Journal of Business Management, 2019)
Agriculture is one of the strongholds of the Indian economy and it accounts for 32% of the Gross Domestic Product (GDP), employing 64% of the country’s workforce.1 Agriculture draws its significance from the fact that it has vital supply and demand links with the manufacturing sector and is a source of livelihood for the rural population of India. To be precise, and it constitutes the backbone of rural livelihood security system. In 2015- 16, India achieved a record food grain production of 227 million tonnes, posing a growth of 20 to 35 million tonnes.